Durability of mortar and concrete containing alkali-activated binder with pozzolans: A review. (15th September 2015) - Hossain, M.M.; Karim, M.R.; Hossain, M.K.; Islam, M.N.; Zain, M.F.M.
Highlights: Durability of mortar/concrete containing pozzolans activated by alkali is reviewed. Water absorption, permeability, porosity, sorptivity and shrinkage are discussed. Chloride, carbonation, corrosion, sulphate and acid resistance are highlighted. Durability of alkali-activated mortar/concrete is compared with the ordinary one. Based on past researches, a few potential studies are suggested for future research. Abstract: Although ordinary Portland cement (OPC) is immensely popular and an essential ingredient for concrete based constructions, it is responsible for the emission of a huge amount of carbon dioxide (CO2 ) in course of its production. In order to reduce the increasing emission of CO2, researchers both in academia and industry have been working on a cement-free alternative sustainable binder using pozzolans such as slag, fly ash (FA), palm oil fuel ash (POFA), metakaolin (MK), rice husk ash (RHA) etc. alongside alkali-activator. A number of researchers have reported that alkali-activated (AA) alumino-silicate materials have the potential to achieve certain mechanical properties such as the compressive strength, elastic modulus and splitting tensile strength in mortar and concrete at early ages of curing with a low energy consumption and low CO2 emission. Most of the researchers have reported that durability of mortar and concrete containing alkali-activated binder (AAB) with the aforementioned pozzolanic materials is superior to that of the conventional mortar and concrete while others are not fully convinced and call for further studies. Based on the previously published works, this paper reviews the current state of knowledge on the durability of mortar and concrete made from the above mentioned pozzolans associated with AAB. Several properties of mortar and concrete including water absorption, permeability, porosity, sorptivity, sulphate resistance, chloride penetration, carbonation, corrosion resistance, drying shrinkage and acid resistance have been discussed. Moreover, a few potential studies have been suggested for the future research.